2014
DOI: 10.1186/cc13838
|View full text |Cite
|
Sign up to set email alerts
|

The plasma level and biomarker value of neutrophil gelatinase-associated lipocalin in critically ill patients with acute kidney injury are not affected by continuous venovenous hemofiltration and anticoagulation applied

Abstract: IntroductionNeutrophil gelatinase-associated lipocalin (NGAL) is a biomarker of acute kidney injury (AKI), and levels reflect severity of disease in critically ill patients. However, continuous venovenous hemofiltration (CVVH) may affect plasma levels by clearance or release of NGAL by activated neutrophils in the filter, dependent on the anticoagulation regimen applied. We therefore studied handling of NGAL by CVVH in patients with AKI.MethodsImmediately before initiation of CVVH, prefilter blood was drawn. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
4
13
0
3
Order By: Relevance
“…The most important difference from previous studies was in the evaluation of the effect of serum NGAL on predicting the optimal time of CRRT discontinuation in our study. Previous study results and our results suggest that serum NGAL is hardly cleared during CRRT and that CRRT does not substantially influence serum NGAL concentration [13][14][15].…”
Section: Comparison With Previous Studiessupporting
confidence: 59%
See 1 more Smart Citation
“…The most important difference from previous studies was in the evaluation of the effect of serum NGAL on predicting the optimal time of CRRT discontinuation in our study. Previous study results and our results suggest that serum NGAL is hardly cleared during CRRT and that CRRT does not substantially influence serum NGAL concentration [13][14][15].…”
Section: Comparison With Previous Studiessupporting
confidence: 59%
“…Compared with serum creatinine and CysC, NGAL has a higher molecular weight and is rarely removed by CRRT [13][14][15]. Therefore, serum NGAL might reflect the recovery of kidney function in patients undergoing CRRT.…”
Section: Introductionmentioning
confidence: 99%
“…Совсем недавно были описаны еще два пептида (NGAL и ADAM9), секретируемые нейтрофилами, ко-торые обладают регуляторным действием на функцию капилляров [29]. Показано, что NGAL (Neutrophil Gelatinase-Association Lipocalin) оказывает индуцирующее влияние на дистальные тубулярные сегменты нефрона почек и может даже служить биологическим маркером острого почечного повреждения [30,39].…”
unclassified
“…While some studies have determined that clearance by the filter in CRRT is low, and have found no evidence of intra-filter release of NGAL by neutrophils [37,38], other studies have demonstrated that NGAL can be adsorbed and filtrated with polysulfone membranes [39]. De Geus et al theorized that larger serum proteins occlude membrane pores preventing the passage of NGAL.…”
Section: Discussionmentioning
confidence: 99%